The Women’s Question among the Masons of Russian Paris - Michela Venditti (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The article is a introduction to the publication of the minutes of the meetings of the Russian lodge "Northern Star" in Paris, concerning the discussion on the admission of women to freemasonry. The proposed archival materials, deposited in the National Library of France in Paris, date back to 1945 and 1948. The women's issue became more relevant after the Second World War due to the fact that Masonic lodges had to recover and recruit new adherents. The article offers a brief overview of the women's issue in the history of Freemasonry in general, and in the Russian emigrant environment in particular. One of the founders of the North Star lodge, M. Osorgin, spoke out in the 1930s against the admission of women. In the discussions of the 1940s, the Masonic brothers repeat his opinion almost literally. Women's participation in Freemasonry is rejected using either gender or social arguments. Russian Freemasons mostly cite gender reasons: women have no place in Freemasonry because they are not men. Freemasonry, according to Osorgin, is a cult of the male creative principle, which is not peculiar to women. Discussions about the women's issue among Russian emigrant Freemasons are also an important source for studying their literary work; in particular, the post-war literary works of Gaito Gazdanov are closely connected with the Masonic ideology.